Rekomendasi Pembimbing Balai Pemasyarakatan Kelas II Kupang Dalam Penanganan Perkara Pencurian Dengan Pemberatan Yang Dilakukan Oleh Anak - Dates, Oyang Tamara (Artemis Law Journal, 2025)
The handling of criminal cases involving children as offenders requires a distinct approach from that applied to adult offenders, particularly in implementing restorative justice principles and child protection measures. This study examines the role and recommendations of the Community Advisor from the Class II Correctional Center (BAPAS) in Kupang in cases of aggravated theft committed by children. Based on the analysis of two cour,t decisions Decision No. 7/Pid.Sus-Anak/2016/PN.Kpg and Decision No. 12/Pid.Sus-Anak/2017/PN.Kpg, it was found that the Community Advisor’s recommendations serve as a critical consideration for judges when imposing conditional sentences. These recommendations include aspects of child rehabilitation, legal protection, child welfare, and environmental factors such as parental neglect in supervising children’s behavior and social interactions. Judges took these recommendations into account to ensure that the imposed sentences were not merely punitive, but also aimed at supporting the child's rehabilitation and social reintegration. These findings affirm the strategic role of Community Advisors and their assessments in the juvenile criminal justice system in safeguarding children's rights and promoting a more humane and preventive sentencing approach.